Infrared-active vibron bands associated with rare gas atom dopants isolated in solid parahydrogen - Raston, P.L.; Anderson, D.T. (Физика низких температур, 2007)
We report high-resolution infrared absorption spectroscopic studies of the dopant-induced Q₁(0) vibron band in solid parahydrogen crystals doped with low concentrations of rare gas atoms. The frequency, lineshape, and integrated absorption coefficient for the rare gas atom-induced Q₁(0) vibron band are measured for Ne, Ar, Kr, and Xe. The observed lineshapes and peak maxima frequencies are sensitive to the H₂ vibrational dependence of the dopant-H₂ isotropic intermolecular potential. Trends observed for Ar, Kr and Xe indicate the vibrational dependence is strong enough for Xe to trap the infrared-active vibron in its first solvation shell while for Ar the vibron remains delocalized. The Ne-induced feature displays a qualitatively different lineshape which is attributed to the weak intramolecular vibrational dependence of the Ne–H₂ intermolecular potential relative to the H₂–H₂ interaction. The lineshapes of the Ar, Kr, and Xe dopant-induced Q₁(0) pure vibrational features agree well with recent first principles calculations.